Influence of Sodium Source and Level on Performance of Second-Cycle Hens Fed Diets with Different Levels of Nonphytate Phosphorus - Waldroup, P.W.; Watkins, S.E.; Hellwig, H.M. (International Journal of Poultry Science, 2005)
Hens of a commercial strain of SCWL hens were subjected to a molt and allowed to resume production before being placed on test diets consisting of a nutritionally complete basal diet supplemented with three sources of sodium (sodium chloride, sodium bicarbonate, and sodium sulfate) at three levels of added sodium (0.10, 0.20, 0.30%) with three levels of nonphytate phosphorus (0.25, 0.45, and 0.65%) in a complete factorial arrangement. When non-chloride sources of sodium were used the diet was supplemented with 0.12% Cl from calcium chloride. A reference group of hens within each level of nonphytate phosphorus was fed a diet with no supplemental sodium or chloride. Each of the thirty resulting dietary treatments was assigned to eight groups of hens, with a replicate group consisting of five 30.5 x 45.7 cm cages with one hen per cage fed from a common feed container. After allowing the hens to acclimate to the test diets for 28 d data were collected for a second 28 d period on rate of egg production, feed intake, egg weight, shell breaking force, and shell deformation time. Results of the study indicate that no more than 266 mg/d of nonphytate P was adequate for egg production. Increasing the dietary P level greater than 0.45% nonphytate P resulted in a significant reduction in egg shell strength. A dietary sodium intake of 128 mg/d appeared adequate to support optimum performance. Use of sodium bicarbonate or sodium sulfate in place of sodium chloride appeared to have no benefits in regard to egg shell strength in this study.